تحقيق التــراث الأدبي بين الاتباع و الابتــداع - تأصيل القدامى و تحديث العرب و المستشرقين - عداد, بوجمعة (جامعة الوادي - University of Eloued, 2021)
هذه الورقة البحثية التي أقدمها بين يدي القارئ الكريم تتمحور حول التراث بمفهومه المعاصر و بالأخص التراث الأدبي و تأصيل تحقيق النصوص عند القدامى، و أهميته عند المحدثين سيما وقد تطورت المناهج وآليات التحقيق ووسائل الطباعة، و جهود المحققين العرب الفردية والجماعية في نشرها مع بيان دور المستشرقين ـــــ إن كان لهم بالطبع من حقّ علينا ـــــ في هذا المجال ولو فضل تنبيهنا إلى أهم معالمنا أو إرشاد باحثينا المحْدَثِين إلى ما غاب عنهم من مناهج التحقيق وآليات الترجمة بفعل تقدّمهم في هذا المجال. Abstract: This research paper which is presented to the honorable reader revolves around the heritage in its contemporary significance, mainly the literary heritage with the reference to texts analysis of the traditional era, besides its importance among the modernists, especially throughout the development of curricula, investigation mechanisms, and the means of printing. In addition, it tackles the individual and collective efforts of the Arab investigators in publication as well as showing the role of orientalists if ever found, of course. Therefore, we are indebted to them for their progress in this field and guide our modern researchers to the missing methods of investigation and translation mechanisms. Key-words: Literary heritage - contemporary - Investigation - Text publication - Orientalism.
مقال
Keywords: التراث الأبي - المعاصر - التحقيق - نشر النصوص - الاستشراق